Ebselen by modulating oxidative stress improves hypoxia-induced macroglial Müller cell and vascular injury in the retina. (July 2015) - Tan, Sih Min; Deliyanti, Devy; Figgett, William A.; Talia, Dean M.; de Haan, Judy B.; Wilkinson-Berka, Jennifer L.
Abstract: Oxidative stress is an important contributor to glial and vascular cell damage in ischemic retinopathies. We hypothesized that ebselen via its ability to reduce reactive oxygen species (ROS) and augment nuclear factor-like 2 (Nrf2) anti-oxidants would attenuate hypoxia-induced damage to macroglial Müller cells and also lessen retinal vasculopathy. Primary cultures of rat Müller cells were exposed to normoxia (21% O2 ), hypoxia (0.5% O2 ) and ebselen (2.5 μM) for up to 72 h. Oxygen-induced retinopathy (OIR) was induced in C57BL/6J mice while control mice were housed in room air. Mice received vehicle (saline, 5% dimethyl sulfoxide) or ebselen (10 mg/kg) each day between postnatal days 6–18. In cultured Müller cells, flow cytometry for dihydroethidium revealed that ebselen reduced the hypoxia-induced increase in ROS levels, whilst increasing the expression of Nrf2-regulated anti-oxidant genes, heme oxygenase 1, glutathione peroxidase-1, NAD(P)H dehydrogenase quinone oxidoreductase 1 and glutamate-cysteine ligase. Moreover, in Müller cells, ebselen reduced the hypoxia-induced increase in protein levels of pro-angiogenic and pro-inflammatory factors including vascular endothelial growth factor, interleukin-6, monocyte chemoattractant-protein 1 and intercellular adhesion molecule-1, and the mRNA levels of glial fibrillary acidic protein (GFAP), a marker of Müller cell injury. Ebselen improved OIR by attenuating capillary vaso-obliteration and neovascularization and a concomitant reduction in Müller cell gliosis and GFAP. We conclude that ebselen protects against hypoxia-induced injury of retinal Müller cells and the microvasculature, which is linked to its ability to reduce oxidative stress, vascular damaging factors and inflammation. Agents such as ebselen may be potential treatments for retinopathies that feature oxidative stress-mediated damage to glia and the microvasculature. Highlights: Ebselen protects against hypoxia-induced injury of retinal Müller cells. Ebselen reduces oxidative stress, vascular damaging factors and inflammation. Ebselen reduces Müller cell gliosis in oxygen-induced retinopathy (OIR). Ebselen reduces neovascularization and vaso-obliteration in OIR.